Measuring the quality of surgical decisions for Latina breast cancer patients. (12th May 2014) - Sepucha, Karen; Feibelmann, Sandra; Chang, Yuchiao; Hewitt, Sarah; Ziogas, Argyrios
Abstract: Background: A high‐quality decision for breast cancer surgery requires that patients are well informed, meaningfully involved in decision making, and receive treatments that match their goals. There is little in the existing literature that examines a comprehensive measure of decision quality for Latina breast cancer patients. Objective: To examine the quality of surgical decisions among Latina breast cancer survivors and explore factors associated with decision quality and decision regret. Design: Cross‐sectional mailed survey. Main outcome measures: English and certified Spanish translations of Breast Cancer Surgery Decision Quality Instrument (BCS‐DQI), Short Acculturation Scale for Hispanics (SASH) and decision regret. Participants and setting: Ninety‐seven breast cancer survivors of Hispanic or Spanish descent identified through the cancer registry from Orange or San Diego Counties in California. Results: The 97 respondents were on average 55.7 years old, 39.1% had high school diploma or more education, and 62.9% had low acculturation (SASH scores < 2.99). The average knowledge score was 48.2%, the average decision process score was 67.5%, and many (77.3%) received treatments that matched their goals. In multivariable models, there were no significant associations with education, age, acculturation and any aspect of decision quality or decision regret in this sample. Respondents who had higher decision process scores, indicating more involvement in decision making, had significantly lower decision regret. Conclusions: The BCS‐DQI may require some adaptation for Latina populations to improve acceptability. The different aspects of decision quality, including knowledge, decision process and concordance, did not vary by level of acculturation.